miR-409 Inhibits Human Non-Small-Cell Lung Cancer Progression by Directly Targeting SPIN1 - Qi Song; Quanbo Ji; Jingbo Xiao; Fang Li; Lingxiong Wang; Yin Chen; Yameng Xu; Shunchang Jiao (Elsevier, 2018)
Lung cancers, the leading cause of cancer mortality worldwide, are characterized by a high metastatic potential. Growing evidence reveals that Spindlin 1 (SPIN1) is involved in tumor progression and carcinogenesis. However, the role of SPIN1 in non-small-cell lung cancer (NSCLC) and the molecular mechanisms underlying SPIN1 in human NSCLC remain undetermined. Here we examined the function of SPIN1 in human NSCLC and found that the expression of SPIN1 was closely correlated with the overall survival and poor prognosis of NSCLC patients. Aberrant regulation of microRNAs (miRNAs) has an important role in cancer progression. We revealed that miR-409 inhibits the expression of SPIN1 by binding directly to the 3' UTR of SPIN1 using dual-luciferase reporter assays. Overexpression of miR-409 significantly suppressed cell migration, growth, and proliferation by inhibiting SPIN1 in vitro and in vivo. SPIN1 overexpression in miR-409-transfected NSCLC cells effectively rescued the suppression of cell migration, growth, and proliferation regulated by miR-409. miR-409 regulates the PI3K/AKT (protein kinase B) pathway in NSCLC. Moreover, clinical data showed that NSCLC patients with high levels of miR-409 experienced significantly better survival. miR-409 expression was also negatively associated with SPIN1 expression. Taken together, these findings highlight that the miR-409/SPIN1 axis is a useful pleiotropic regulatory network and could predict the metastatic potential in NSCLC patients early, indicating the possibility that miR-409 and SPIN1 might be attractive prognostic markers for treating NSCLC patients. Keywords: non-small lung cancer, NSCLC, miR-409, SPIN1, therapy